Why Religion Matters: Montenegro’s Sacred Nationhood in a Time of Contestation - Francesco Trupia (Colloquia Humanistica)
This book review offers a critical assessment of Emil Hilton Saggau’s Nationalisation of the Sacred. Although Saggau’s work seems to propose a concise history of Montenegro through the lens of Orthodox historiography, the main argumentation provides sobering perspectives that unravel a wealth of religious and political issues in Montenegro and South-East Europe in general.